Selective suppression of retroviral gp70-anti-gp70 immune complex formation by prostaglandin E1 in murine systemic lupus erythematosus (The Rockefeller University Press, 1980)
The effect of pharmacologic quantities of prostaglandin E1 (PGE) was investigated in three strains of mice (NZB X NZW, MRL/1, and BXSB) that spontaneously develop lupus-like glomerulonephritis. PGE-treatment prolonged survival and retarded the glomerular deposition of immune complex (IC) and the development of glomerulonephritis in NZB X NZW and MRL/1 mice, but did not similarly protect BXSB mice. Changes in the responsive strains correlated well with reduced amounts of circulating gp70 complexed with anti-gp70 antibodies compared with untreated controls, although total concentrations of gp70 (free and complexed) detectable in sera were similar in both groups of mice. The results strongly suggest that: (a) PGE selectively suppressed the immune response to retroviral gp70, (b) PGe had little effect on the quantity or quality of anti-DNA antibodies but did reduce the deposition of anti- DNA containing IC in the kidneys, and (c) gp70 IC appear to play an important role in the pathogenesis of glomerulonephritis in murine systemic lupus erythematosus.